Tabanidae insect (horsefly and deerfly) allergy in humans: A review of the literature. Issue 8 (23rd June 2020) - Whyte, Andrew F.; Popescu, Florin‐Dan; Carlson, John
Abstract: Allergy to insects of the family Tabanidae (order Diptera), commonly called horseflies or deerflies, is anecdotally common, although the published literature is limited to case reports and small case series. This review summarizes the available literature, in which there is enormous variability in clinical detail, identification of species or even genus, and means and thoroughness of assessment of sensitization. The clinical utility of in vivo and in vitro assays remains unclear. Investigation and management of patients reporting anaphylaxis to suspected bites must therefore be pragmatic, by considering other insects (eg Hymenoptera), provision of a written action plan and self‐injectable adrenaline if appropriate, and advice on avoidance.